A study of surgically managed ruptured ectopic pregnancies in a rural medical college hospital over a period of 5 years - Patra, Kajal Kumar; Majumder, Siddhartha; Chattopadhyay, Shibram; Samanta, Poulami (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Although ectopic pregnancy is of interest to the embryologist, general practitioner, obstetrician, and abdominal surgeon for various reasons, our present study was undertaken to determine the incidence, epidemiological characteristics, clinical features, risk factors, diagnosis, management and operative findings of ectopic pregnancies at our hospital. Methods: This is a retrospective study of ectopic pregnancies that were managed operatively at Bankura Sammilani Medical College and Hospital from April 2013 to April 2018. Unruptured tubal ectopic pregnancy that were managed medically are excluded in this study. Results: The incidence of ectopic pregnancy was 0.59%, and the peak age of incidence was 20-25 years (33.84%) with third gravidas (46.3%) being most commonly affected. The most common symptoms were amenorrhea (96.92%), abdominal pain (90.76%), and vaginal bleeding (11.53%) and the most common signs were pallor (46.30%), shock (38.46%), and cervical motion tenderness (33.84%). Most common risk factors were past history of tubectomy (66.61%). The commonest site for tubal ectopic pregnancy was ampullary in 545 cases (84.89%). Salpingectomy done in 553 cases (85.07%) was the most commonly performed operation for ruptured tubal ectopic pregnancy. Conclusions: In the surgical management of ectopic pregnancy, the benefits of salpingectomy over salpingostomy are uncertain. The early diagnosis of an ectopic pregnancy reduces the presentation to response time, which is crucial in determining the morbidity, mortality and long-term effects for the patient. Although with earlier diagnosis, medical therapy with methotrexate can be offered and surgery avoided in some women, the best regimen remains unclear. There have been advances made in the management of ectopic pregnancy but there are still questions to be answered.